Corporate Social Responsibility in Sustainable Tourism Development towards Local Culture - Chao Stephen Wu; Zhang Shen Tan; Liu Tsai Lee; Shen Xiong Hoa; Giovine Girard Fordham (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2023)
As the global tourism industry expands, the delicate equilibrium between economic growth and the preservation of local cultures faces increasing challenges. This research explores the integration of Corporate Social Responsibility (CSR) principles into sustainable tourism development as a means to safeguard and promote local cultures. The study synthesizes concepts from cultural preservation, sustainable tourism, and CSR to construct a comprehensive framework. Findings highlight that CSR can catalyze cultural preservation by promoting authenticity, empowering local communities, and fostering responsible tourism practices. Challenges such as cultural commodification and the need for ongoing cultural sensitivity education are acknowledged. The research emphasizes the necessity of balancing economic objectives with cultural preservation and underscores the potential for transformative shifts in industry paradigms. Practical guidelines for implementation, the role of education, and collaboration among stakeholders are discussed. The study contributes to an enhanced understanding of how CSR can harmonize economic interests and cultural preservation, offering a blueprint for a more ethical, culturally respectful, and sustainable future for the tourism industry